Dezocine, An Opioid Analgesic, Exerts Antitumor Effects in Triple-Negative Breast Cancer by Targeting Nicotinamide Phosphoribosyltransferase - Xue, Chenyang; Chen, Wei; Yuan, Aiwu; Chen, Cheng; Li, Shuaihu; Chen, Kai; Zhao, Yang; Xiao, Tian; Shao, Genze; Zou, Yongdong; Zheng, Duo (Frontiers in Pharmacology, 2021)
Opioids are a potential adjuvant treatment for certain cancers; while they are primarily used to relieve chronic pain, these drugs may also affect cancer progression and recurrence. Dezocine is one opioid commonly used in China, but its effects on cancer cells are unknown.Here, we demonstrated the inhibitory effect of dezocine ontriple-negative breast cancer (TNBC) cells, and determined the underlying molecular mechanism. We found that dezocine suppressed cell proliferation, migration and invasion, and induced apoptosis in TNBC cells. Xenograft models demonstrated the inhibitory effects of dezocine treatment on TNBC tumor growth in vivo.The anticancer effects of dezocine were independent ofopioid receptors, which are not highly expressed by normal breast or breast cancer tissues. A pull-down assay and LC-MS/MS analysis indicated that dezocine directly targets NAMPT: computer modeling verified that the free energy of dezocine kinetically bound into the pocket of NAMPT was -17.4 kcal/mol. Consequently, dezocine treatment inhibited NAMPT enzyme activity, resulting in cellular NAD abolishment. We confirmed thedezocine-induced inhibition of cell proliferation by both NAMPTknockdown and upon treatment with the inhibitor FK866.Our results suggest that both dezocine and NAMPT mightrepresent novel therapeutic targets for TNBC.